sensitivity experiment using CESM POP2 - Gu, Sifan; Liu, Zhengyu (Zenodo, 2023)
CTRL.nc for control experiment. NoWind.nc: an experiment in which the North Atlantic (40N-60N) surface wind is suppressed to 1%. FB.nc : for the experiment in which the North Atlantic bottom topography is set to flat. The depth of North Atlantic between 0°N and 50°N is set to 4375-m uniformly. FB_NoWind.nc : an experiment in which the North Atlantic bottom topography is set to flat as FB.nc and the North Atlantic surface wind is suppressed to 1%. NA_0.01Wind.nc: an experiment in which the North Atlantic (north of 15N) surface wind is suppressed to 1%. 15N-45N.nc :an experiment in which the North Atlantic (15N-45N) surface wind is suppressed to 1%. 45N-60N.nc : an experiment in which the North Atlantic (45N-60N) surface wind is suppressed to 1%. 40N-50N.nc: an experiment in which the North Atlantic (40N-50N) surface wind is suppressed to 1%. 50N-60N.nc: an experiment in which the North Atlantic (50N-60N) surface wind is suppressed to 1%. Wind_NoTilt.nc: t he zonal mean wind stress of CTRL is applied over north of 15ºN in the North Atlantic. NA_0.5Wind.nc: s urface wind stress is set to 50% over north of 15 ºN in the North Atlantic. NA_0.1Wind.nc: s urface wind stress is set to 10% over north of 15 ºN in the North Atlantic. CTRL_R1.nc: CTRL_R1 is the control experiment under CORE-II forcing with 1-degree resolution. NoWind_R1.nc: this experiment applies 1% wind stress of the control value over 40ºN-60ºN in the North Atlantic with1-degree resolution . FFB_R1.nc: this experiment is with no MAR bottom topography setting with the depth of North Atlantic between 0°N and 50°N set to 4375-m uniformly with 1-degree resolution.